2019
DOI: 10.1021/acsaem.9b00669
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Strategy to Fabricate Metal Sulfides@Carbon Fibers As Freestanding and Flexible Anodes for High-Performance Lithium/Sodium Storage

Abstract: The future trend toward flexible electronics creates a demand for flexible power sources using rechargeable batteries, where freestanding and flexible electrodes are of critical importance. The utilization of high capacity anode materials like metal sulfides in flexible batteries is highly desirable for the miniaturization of electronic devices but is nevertheless very challenging in the fabrication of an electrode that is freestanding and flexible. Herein, a universal electrospinning strategy to fabricate fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Meanwhile, they usually exhibit high energy density, high mechanical stability, and good flexibility. In this regard, the flexible films with layered V 3 S 4 embedded in carbon nanofiber (V 3 S 4 @CNF), [ 161 ] Co 9 S 8 nanoclusters embedded in honeycomb‐like S‐doped C foam (Co 9 S 8 @SCF, Figure 15K), [ 162 ] Co 9 S 8 Ni 3 S 2 nanoparticles embedded in S‐doped C nanofiber networks (Ni 3 S 2 /Co 9 S 8 @SCNF), [ 163 ] Ni 3 S 2 or Fe 7 S 8 nanoparticles embedded in continuous and interwoven carbon fibers (Ni 3 S 2 /C or Fe 7 S 8 /C), [ 164 ] and Fe 7 S 8 microparticles well‐welded on 3D‐cross‐linked carbon networks and embedded in highly conductive rGO film (CFG, Figure 15L) [ 126 ] were designed to improve Na + /Li + storage properties.…”
Section: Strategy For Enhancing Electrochemical Performancementioning
confidence: 99%
“…Meanwhile, they usually exhibit high energy density, high mechanical stability, and good flexibility. In this regard, the flexible films with layered V 3 S 4 embedded in carbon nanofiber (V 3 S 4 @CNF), [ 161 ] Co 9 S 8 nanoclusters embedded in honeycomb‐like S‐doped C foam (Co 9 S 8 @SCF, Figure 15K), [ 162 ] Co 9 S 8 Ni 3 S 2 nanoparticles embedded in S‐doped C nanofiber networks (Ni 3 S 2 /Co 9 S 8 @SCNF), [ 163 ] Ni 3 S 2 or Fe 7 S 8 nanoparticles embedded in continuous and interwoven carbon fibers (Ni 3 S 2 /C or Fe 7 S 8 /C), [ 164 ] and Fe 7 S 8 microparticles well‐welded on 3D‐cross‐linked carbon networks and embedded in highly conductive rGO film (CFG, Figure 15L) [ 126 ] were designed to improve Na + /Li + storage properties.…”
Section: Strategy For Enhancing Electrochemical Performancementioning
confidence: 99%
“…[35,105] For example, the free-standing SnS electrode with embedded nanoparticles in carbon nanofibers exhibits a longer life cycle and a better rate performance for sodium storage in comparison with conventional SnS electrode. [106] Free-standing configuration designs were also realized with other CA materials, such as SnS 2 nanosheets stacking on graphene. [87] This flexible free-standing electrode displayed satisfactory energy and power density, cycle life, and mechanical stability, which is a great inspiration for the future study of flexible batteries and devices.…”
Section: Electrode Configuration Designmentioning
confidence: 99%
“…In this regard, various synthesis strategies such as hydrothermal (Zhao, Xu, et al, 2020), microwave, ball milling (Karuppannan et al, 2020), chemical layer deposition (Madito et al, 2020), atomic layer deposition (Ansari et al, 2019), electrochemical synthesis (Zhang, Cai, et al, 2018), electrodeposition (Zhao et al, 2019) have been adopted tailor the morphologies of MS to receive desired performance. In addition, research has also focused on exfoliation (Li et al, 2014;Nicolosi et al, 2013) for electrode strategy along with not so vastly reported electrospinning (Du et al, 2019). One of the prioritizing factors considered is interlayer spacing for efficient ionic transport.…”
Section: Ms As Efficient Electrode Materials For Scsmentioning
confidence: 99%